Validation of the Chinese Empowerment of Parents in the Intensive Care (EMPATHIC-30) Questionnaire Among Parents in Neonatal Intensive Care Units: A Prospective Cross-Sectional Study - Zhuang, Yan; Zhang, Rong; Gao, Xi-rong; Zhu, Li-hui; Latour, Jos M. (Frontiers in Pediatrics, 2022)
Background: There are no specific validated questionnaires assessing satisfaction of family-centered care experienced by parents of infants hospitalized in Chinese Neonatal Intensive Care Units (NICU). Aim: To adapt and test the reliability and validity of the Chinese version of the EMPATHIC-30 questionnaire in NICU settings. Methods: A prospective, cross-sectional design was adopted. The EMPATHIC-30 questionnaires were completed by parents of infants admitted to one of the four NICUs at Hunan Children’s Hospital, China, between November 2018-2019. Inclusion criteria were parents whose infants were admitted to the NICU for at least 5 days. Exclusion criteria were parents whose child was discharged within 5 days after admission or whose infants died in the NICU. Reliability was tested with the Cronbach’s alpha. The congruent validity was tested using Spearman’s Rank correlation analysis and the non-differential validity was tested using Cohen’s d. Results: Parents of 619 infants discharged from the NICUs completed and returned the questionnaire. Most infants were male (n=337, 54.4%) and infants’ length-of-stay was a median of 21 days (IQR=14-37). Mostly mothers completed the questionnaire (n=523, 84.5%). The Cronbach’s alpha values of the five individual domains were between 0.67 and 0.95 and the alpha of the total questionnaire was 0.90, providing an adequate internal consistency. Congruent validity was measured by correlating the five domains with four standard satisfaction scales, documenting an weak correlation (rs -0.025 to 0.327). Non-differential validity showed some significant effect size between four binary variables (mechanical ventilation, unplanned admission, admission after surgery, length-of-stay) four of the five domains. Conclusion: The Chinese version of EMPATHIC-30 questionnaire showed acceptable psychometric properties. This instrument might be considered a suitable instrument to measure parent satisfaction among Chinese parents whose infant is admitted to a NICU. Measuring parent satisfaction with this instrument might contribute to improving family-centered care initiatives in NICUs with Chinese parents.